Amazon Web Services in action - Wittig, Michael; Wittig, Andreas, 1984- (Manning Publications, 2023)
In Video Editions the narrator reads the book while the content, figures, code listings, diagrams, and text appear on the screen. Like an audiobook that you can also watch as a video. Master essential best practices for deploying and managing applications on Amazon Web Services. This revised bestseller is packed with techniques for building highly available and scalable architectures and automating deployment with Infrastructure as Code. Leverage globally distributed data centers to launch virtual machines with EC2 Store and archive large volumes of data with EBS, S3, and EFS Persist and query data with highly available and scalable database systems with RDS and DynamoDB Enhance performance with caching data in-memory with ElastiCache and MemoryDB Use Infrastructure as Code to automate your cloud infrastructure Secure workloads running in the cloud with VPC and IAM Build fault-tolerant web applications with ALB and SQS Automate common sysadmin tasks with Lambda, CLI, and SDK Build cloud-native applications based on containers with AppRunner, ECS, Fargate Thousands of developers have chosen Amazon Web Services in Action: An in-depth guide to AWS to help them succeed with the AWS cloud. Readers love this all-practical handbook for its complete introduction to computing, storage, and networking, along with best practices for all core AWS services. This revised third edition features new chapters on containerization, along with a variety of AWS innovations. You'll also learn how automating your infrastructure with IAC is a game changer for your cloud deployment, delivering a massive boost to efficiency and quality. About the Technology Amazon Web Services, the leading cloud computing platform, offers customers APIs for on-demand access to computing services. Rich in examples and best practices of how to use AWS, this Manning bestseller is now released in its third, revised, and improved edition. About the Book In Amazon Web Services in Action, Third Edition: An in-depth guide to AWS , the Wittig brothers give you a comprehensive, practical introduction to deploying and managing applications on the AWS cloud platform. With a sharp focus on the most important AWS tasks and services, they will save you hours of unproductive time. You'll learn hands-on as you complete real-world projects like hosting a WordPress site, setting up a private cloud, and deploying an app on containers. What's Inside Leverage globally distributed data centers to launch virtual machines Enhance performance with caching data in-memory Secure workloads running in the cloud with VPC and IAM Build fault-tolerant web applications with ALB and SQS About the Reader Written for mid-level developers, DevOps or platform engineers, architects, and system administrators. About the Author Andreas Wittig and Michael Wittig are software engineers and consultants focused on AWS. Together, they migrated the first bank in Germany to AWS in 2013. Quotes Up-to-date coverage. Code examples and configurations are all excellent. Even containerization is very well explained. This is the bible for Amazon Web Services. - Mohammad Shahnawaz Akhter, Bank of America It has never been so easy to learn AWS. - Jorge Ezequiel Bo, TravelX Essential for those who decide to embark on the Amazon cloud journey. - Matteo Rossi, UnipolSai Assicurazioni A complete introduction to the most important AWS Services with very useful practical examples. - Matteo Battista, GamePix.